Evaluation of the Application of Distance Learning Programs in Madrasah Aliyah Malang Regency - Kadir, Abdul; Umiarso, Umiarso (Jurnal Pendidikan Agama Islam, 2021)
Distance learning during the pandemic is a new strategy in the world of education. The purpose of this research is to measure and assess the success rate of distance learning implementation at Madarasah Aliyah in Malang district. This type of research is an evaluation research. The subjects of this study amounted to 10 people consisting of teachers and school principals from three Aliyah madrasas in the Malang area. The sampling technique used purposive sampling. Methods of data collection using interviews and observation. The data analysis technique uses the CIPP model with stages, namely preparation, implementation, completion and reporting. This study concludes the results in the form of four important points. First, not all schools can carry out the distance learning process optimally. Second, teachers do not have uniform competence and can determine suitable learning strategies. Third, the evaluation of distance learning outcomes has not been able to fully describe students' abilities. Fourth, the obstacles faced in the form of teacher readiness and student learning motivation. This study still has many limitations, both in terms of research procedures, themes raised or the type of research taken. Subsequent research conducted will enrich similar research themes.